P128 Human papillomavirus (HPV) vaccination in young men who have sex with men (MSM) in the UK. An online survey of attitudes, intentions and opinions among MSM offered vaccination within integrated sexual health services. (30th June 2016) - McSorley, John; Zhou, Tapiwa; Kuria, Patrick; Kapembwa, Moses; Brook, Gary
Abstract : Background: We have offered quadrivalent HPV vaccine (HPV4) to MSM under 27 years since 2012. We have observed a 60% 3 dose completion rate within 1 year. Aims: (1) To identify motivating factors or barriers influencing HPV4 completion in a cohort of MSM receiving at least one dose of HPV vaccine. (2) To identify factors influencing survey response rates. Methods: An email and reminder and an SMS text weblink to an online survey was sent to all MSM who received at least 1 dose of HPV4 vaccine. Results: Of 893 eligible, 688 (77%) had an email address, 257 (29%) opened the survey, and 228 (26%) completed the survey. 89% respondents learned of the vaccine at offer. 87% were happy with the information received and 97% with their decision to accept vaccine. A reminder strategy utilising SMS text for 1 year was preferred. Prevention of genital warts and anogenital cancers were equally highly important in motivation. Trusted healthcare workers were important influences in decision making Survey respondents were more likely to be older (>21 yrs), HIV positive, homosexual and of non-white british ethnicity than the cohort of vaccine recipients. Discussion: MSM HPV vaccine recipients express high levels of satisfaction with vaccination despite little a priori awareness. Trusted public service providers & friends are influential. Completion should be supported through a multifaceted approach involving a range of agencies and media and expansion of access to vaccine.